Hubungan Pengetahuan Dan Perilaku Dengan Frekuensi Kejadian Penyakit Kulit Pada Masyarakat Pengguna Air Kuantan - Siti - Rahmayani; Siti Rahmalia HD; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aims of this research was to identify of correlation between knowledge and behavior of the frequency of occurrence of skin diseases on society Kuantan River users. The design is a correlation with cross sectional approach. The sample was 65 respondents taken based on inclusion criteria using purposive sampling. Measuring instrument used a questionnaire after Validity (knowledge p=0,585>0,444 and behavior p=0,546>0,444) and reliability test (knowledge p=0,969>0,444 and behavior p=0,937>0,444). The univariate analysis was done by looking at the distribution of frequency and bivariate analysis was done by using chi-square test. The results showed less knowledge (73,3%) respondents about skin diseases with frequency occurrence 1-4 times in years. Statistic results showed no correlation between knowledge and the frequency of occurrence of skin diseases p value 1,000 (α > 0,05), Odds Ratio 1,455. The results showed also who had bad behavior about used Kuantan River (29,5%) with frequency occurrence of skin diseases 1-4 times in years. Statistic test showed p value 0,001 < 0,05, there is a correlation between the behavior of the frequency of occurrence of skin diseases with OR 0,145. To minimize of high of the to frequency occurrence of skin disease, Koto Benai community don’t use Kuantan’s River Water to activity everyday. Keywords: behavior, frequency of skin diseases, knowledge.